Comparative Study of Longitudinal Temperature Decay of Weak and Strong Plumes with Different Tunnel Aspect Ratios - Zhisheng Li; Xin Liu; Yanying Cheng; Gang Li; Dong Xu; Wei Hou; Rui Zheng; Baiyi Li (Fire)
Numerical investigations were performed to compare and analyze the effect of the tunnel aspect ratio on the temperature distribution caused by weak and strong plumes. Four tunnel aspect ratios were chosen, which were one, two, four, and eight, respectively. The heat release rates were manipulated within the range of 3 MW to 50 MW in order to replicate fire situations involving small cars, trucks, and big freight vehicles. The study revealed that the aspect ratio of the tunnel has minimal impact on the temperature distribution in the vicinity of the fire area, but it significantly affects the temperature distribution in the distant area from the fire source. The temperature gradient of the fire source at a distance exhibits a non-monotonic tendency in the far-field. The temperature distribution gradient decreases more significantly when driven by a strong plume compared to a weak plume. A quantified investigation of the maximum excess temperature was conducted by including a specific diameter for the fire source. Subsequent correlations of the longitudinal temperature distribution were established for both weak and strong plumes.